Models for solar radiation prediction based on different measurement sites. (March 2015) - Lazzaroni, Massimo; Ferrari, Stefano; Piuri, Vincenzo; Salman, Ayşe; Cristaldi, Loredana; Faifer, Marco
Highlights: We describe experiments for solar radiation prediction based on different approach. The models provided comparable average prediction error below persistence error. Remote data captured allows short-term prediction and maintenance scheduling. Abstract: The modeling of solar radiation for forecasting its availability is a key tool for managing photovoltaic (PV) plants and, hence, is of primary importance for energy production in a smart grid scenario. However, the variability of the weather phenomena is an unavoidable obstacle in the prediction of the energy produced by the solar radiation conversion. The use of the data collected in the past can be useful to capture the daily and seasonal variability, while measurement of the recent past can be exploited to provide a short term prediction. It is well known that a good measurement of the solar radiation requires not only a high class radiometer, but also a correct management of the instrument. In order to reduce the cost related to the management of the monitoring apparatus, a solution could be to evaluate the PV plant performance using data collected by public weather station installed near the plant. In this paper, two experiments are conducted. In the first, the plausibility of the short term prediction of the solar radiation, based on data collected in the near past on the same site is investigated. In the second experiment, the same prediction is operated using data collected by a public weather station located at ten kilometers from the solar plant. Several prediction techniques belonging from both computational intelligence and statistical fields have been challenged in this task. In particular, Support Vector Machine for Regression, Extreme Learning Machine and Autoregressive models have been used and compared with the persistence and the k -NN predictors. The prediction accuracy achieved in the two experimental conditions are then compared and the results are discussed.